Fuzzy Treatment applied Energy Control Solar Cooker (International Journal of Food and Nutritional Sciences, 2021)
This study was created to examine the fuzzy logic principles used in the thermal energy assessment of a box-style solar cooker under the specific meteorological conditions in Chennai, Tamilnadu, India. With containers made of copper, aluminum, bottom side, and bar plate coated in black paint & (Al2O3) for the system, various cooking tests of food items have been produced. The following fuzzy logic rules are specifications. It is accepted to provide the manufacturer with a brief window of opportunity for improving the cooker.